Inﬂuence of the Edge Effect on a Soil Seed Bank of a Natural Fragment in the Atlantic Forest - Machado, Felipe Santana; França, Ana Cristina Magalhães de; Santos, Rubens Manoel dos; Borém, Rosângela Alves Tristão; Guilherme, Luiz Roberto Guimarães (Iheringia, Série Botânica., 2017)
The edge eff ect is defi ned as the change of biotic and abiotic characteristics in the fi rst meters of a forest fragment from the edge towards its interior. In fragments formed by human activities, this change generates increased richness and abundance, as well as changes in the structure of the forest species of soil seed bank in the border region. This study demonstrates that in natural fragments of cloud forests, the abundance and richness positively infl uence the linear relation from the edge to interior, mainly by distances of 120 and 180 meters from the edge. This eff ect can be a result of new plant growth, or ‘pioneer’ occupation in gaps in the forests generated by large fallen trees.